Perception of Malaysian learners on the use of written communication strategies in Mandarin, French and Japanese - Abdul Halim, Hazlina; Ang, Lay Hoon; Mamat, Roslina; Abd Rahim, Normaliza (Canadian Center of Science and Education, 2014)
This study aimed to investigate the perception of Malaysian learners on the use of written communication strategies in French, Mandarin and Japanese language learning. The subjects consisted of 2nd and 3rd year Malaysian students at Universiti Putra Malaysia. A total of 173 subjects participated in this study. The main instrument used was a 2-section questionnaire on the demographic and the perception on the use of written communication strategies. The items for the questionnaires on the perception of learners on communication strategies were adapted from Dörnyei (1995) Taxonomy of Communication Strategies. The overall findings indicated that the learners perceived to be using the written communication strategies moderately. The results across the three languages further indicated that ‘appeal for help’ and ‘topic avoidance’ were perceived to be frequently used by French, Mandarin and Japanese learners. It was suggested that further intensive research should be conducted to look into the commonly used communication strategies to develop a comprehensive framework for the incorporation of communication strategy in French, Mandarin and Japanese language learning instruction, materials and tasks for Malaysian learners.